2021
DOI: 10.1016/j.contraception.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Two prophylactic pain management regimens for medical abortion ≤63 days' gestation with mifepristone and misoprostol: A multicenter, randomized, placebo-controlled trial

Abstract: Objective: To determine if either prophylactic tramadol 50 mg or ibuprofen 400 mg/metoclopramide 10 mg result in lower maximal pain compared to placebo in women ≤63 days' gestation having a mifepristone-misoprostol medical abortion. Study design: We conducted a randomized, placebo-controlled trial in Nepal, South Africa, and Vietnam. Participants seeking medical abortion received active treatment or placebo, taken at time of misoprostol and repeated 4 hours later. All had access to additional analgesia. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…We were only able to offer a single antiemetic in the form of oral cyclizine during this study. There may be other antiemetics that are better suited to managing nausea during medical abortion, such as metoclopramide, 24 but further study is required.…”
Section: Discussionmentioning
confidence: 99%
“…We were only able to offer a single antiemetic in the form of oral cyclizine during this study. There may be other antiemetics that are better suited to managing nausea during medical abortion, such as metoclopramide, 24 but further study is required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intake of ibuprofen (600 mg) 1 hour before the use of misoprostol could be helpful in reducing both fever and abdominal pain [28] . Previous reports also indicated that ibuprofen (600 mg) could be taken every eight hours in severe cases to avoid high temperature and abdominal pain [29][30][31] . In addition, since misoprostol was a prostaglandin E1 analogue, it might have bene ts in relieving gastric or duodenal ulcers [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Although supplemental narcotics have limited value, they may be also prescribed. 13 Various painkillers are used to relieve post-abortion pain, the most important of which are opioids. Although opioids are very effective in controlling abortion-related pain, because of their side effects such as drowsiness, nausea and vomiting, ileus, constipation, respiratory suppression, central nervous system inhibition and even addiction, researchers try to identify other analgesic medications with acceptable efficacy along with higher safety.…”
Section: Introductionmentioning
confidence: 99%